Millennial makeover MySpace, YouTube, and the future of American politics - Winograd, Morley (Rutgers University Press, 2008)
Change in the 2008 election will cause another of our country's periodic political makeovers resulting from the coming of age of the Millennial Generation and the full emergence of the Internet-based communications technology that this generation uses so well.